PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA DIKANTOR BADAN PENGELOLAAN KEUANGAN PENDAPATAN DAN ASET DAERAH KABUPATEN NIAS SELATAN - Safurugara, Hatinia (PARETO : Jurnal Riset Bisnis dan Manajemen, 2024)
This study aims to determine the influence of organizational culture and compensation, both partially and simultaneously, on employee job satisfaction at the Office of the Regional Financial Management Agency of South Nias District. This research used a quantitative approach. The population and sample comprised all employees of the Office of the Regional Financial Management Agency of South Nias District, with a saturated sampling technique determining 45 respondents. The instrument used was a questionnaire. The data analysis technique employed was multiple linear regression analysis. The results of this study indicate that organizational culture and compensation have a positive and significant influence on employee job satisfaction at the Office of the Regional Financial Management Agency of South Nias District, both partially and simultaneously. The conclusions drawn are (1) organizational culture has a positive and significant influence on employee job satisfaction at the Office of the Regional Financial Management Agency of South Nias District, (2) compensation has a positive and significant influence on employee job satisfaction at the Office of the Regional Financial Management Agency of South Nias District, and (3) organizational culture and compensation simultaneously have a positive and significant influence on employee job satisfaction at the Office of the Regional Financial Management Agency of South Nias District. Recommendations from this study include the need for better supervision of task implementation among all employees, clarity in task assignments, leadership encouragement of employees, and organizing gatherings to foster good teamwork among employees.